Temporomandibular joint meniscopexy with mitek mini anchors (2011)
The purpose of this study is to show long-term results with the use of Mitek mini anchors (DePuy Mitek, Raynham, MA) in the surgical treatment (meniscopexy or discoplasty) of internal derangements that lead to a dysfunctional temporomandibular joint (TMJ). We evaluated 50 patients, 32 women and 18 men, ranging in age from 19 to 53 years, with a mean age of 33.5 years. All patients included in the study were diagnosed with anterior disc displacement without reduction. Each patient underwent surgical meniscopexy and placement of Mitek mini anchors with No. 2-0 nylon monofilament sutures. The variables taken into account in this study include range of mouth opening, painful symptoms (evaluated with the visual analog verbal scale), and the presence of any clicks in the TMJ. Preoperative analysis showed painful symptoms in 100% of evaluated patients, the presence of clicks of the TMJ in 76%, and a mean mouth opening range of 23.5 mm. Postoperative analysis showed that 92% of the patients had no painful symptoms, 90% did not have any associated clicks in the TMJ, and the mean mouth opening range on postoperative evaluation was 38.3 mm, with a mean increase of 14.8 mm. We conclude that surgical placement of Mitek mini anchors represents an alternative that can be considered a tool of great utility for discoplasty procedures, showing evident clinical improvement.